The Effectiveness of Smart Multiplication Table Media (Talintar) in Improving Understanding of Multiplication Concepts - Ade Mulyanti; Edhy Rustan; Sumardin Raupu (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
Understanding the concept of multiplication is a basic competency that must be mastered by elementary school students as a foundation in learning more complex mathematical concepts. However, the low understanding of the concept of multiplication is still a problem in the learning process so that learning media are needed that can help students understand the concept more concretely. This study aims to analyze the effectiveness of the use of Smart Multiplication Table Media (Talintar) in improving the understanding of the concept of multiplication of grade III students of SD Negeri 64 Tobulung. This study uses a quantitative approach with a quasi-experimental design of the pretest-posttest control group design. The research sample was 45 students selected using cluster random sampling techniques. Data were collected through observation and tests, then analyzed using descriptive and inferential statistics. The results of the study showed that the implementation of learning using Talintar media was in the very good category. The average pretest score of the experimental class increased from 35.10 (very poor category) to 87.50 (good category) in the posttest, while the control class only increased from 30.97 (very poor category) to 62.28 (poor category). The results of the hypothesis test showed a Sig. value. (2-tailed) = 0.000 (<0.05), which indicates a significant difference between the experimental class and the control class. Thus, the Talintar media has been proven effective in improving the understanding of multiplication concepts of grade III students at SD Negeri 64 Tobulung and can be an alternative mathematics learning media in elementary schools.